“If everyone comes together, many things can be changed”: A qualitative study on men’s perspectives on menstrual health and equity in the Barcelona area (Spain) - Andrea García-Egea; Constanza Jacques-Aviñó; Anna Berenguera; Jordi Baroja-Benlliure; Diana Pinzón-Sanabria; Anna Sofie Holst; Tomàs López-Jiménez; Jordina Munrós-Feliu; María Mercedes Vicente-Hernández; Carme Valls-Llobet; Cristina Martínez-Bueno; Laura Medina-Perucha (PLoS ONE, 2025)
There is a paucity of research exploring how men and individuals who do not menstruate comprehend menstrual health and equity. The objective of this study was to explore the conceptualization and attitudes towards menstruation and the menstrual cycle among men and people who do not menstruate aged between 18 and 55 in the Barcelona area. Furthermore, it examined their involvement in menstrual health and equity initiatives. This qualitative study employed a feminist critical perspective. Seventeen semi-structured photo-elicitation interviews were conducted. It was frequently observed that menstrual education was often inadequate and biomedical in nature. Participants often acquired knowledge about menstruation through interactions with menstruating sex-affective partners. Menstruation was generally perceived negatively, and menstrual taboo and stigma were apparent. Some participants expressed the view that men should raise awareness of a more positive stance on menstruation. The findings of this study highlight the need for structural menstrual policies and community programs where men and people who do not menstruate are involved.